(untitled) (Revista Brasileira de Ciências Farmacêuticas, 2004)
The consumption of medicinal plants has increased during the last years. The purpose of this study was to evaluate and identify fungi specimens present in samples of Cassia acutifolia Delile (20) (sene) and Peumus boldus (Molina) Lyons (Boldo-do-Chile) (20), that were purchased in drugstores and markets of Campinas, Brazil, by usual methods. The results showed that 45% of samples did not fit the minimum quality standards recommended by the World Health Organization (WHO). No differences were observed in the quantitative analysis between the samples sold at the drugstores and at the markets. The identified genera and species of fungi were: Aspergillus, Penicillium, Phoma, Cladosporium, Trichoderma, Rhizopus, Mucor, Aureobasidium pullulans, Mycelia sterilia, Acremonium and Monilia sitophila. Considering the level of contamination and the presence of Aspergillus and Penicillium, which are able to produce mycotoxins, there is an urgent need for quality control of the phytotherapic products in order to assure their efficacy and safety.